Peningkatan Minat Literasi Siswa SD Negeri Teganing Melalui Program Zona Literasi Kreatif - Isnaini, Reynata; Durrotunnaschichah, Nur Roo’iqoh; Ambarwati, Zulvara Ari; Al Reza, Prima Reza; Setiawan, Angga Febri; Khoirurrohman, Fata; Shafira, Nabila; Aisya, Selqly Ruwana; Meilyanto, Achmad Mauluddin Dwi; Mahardika, Abi Esa; Anugrah, Rinasa Agistya (Universitas Muhammadiyah Yogyakarta, 2025)
The service program aims to increase students' interest in literacy at SD Negeri Teganing through the Creative Literacy Zone program. The main problem faced by the school is the low interest in reading due to the lack of library facilities and unattractive book collections. The method used in this program is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which involves various stages ranging from needs analysis to evaluation of program effectiveness. The main activities included literacy counseling, creation of a creative literacy zone, socialization of literacy tree filling, and a literacy competition titled Rangkaian Warna Rajutan Cerita. Survey results showed a significant increase in students' interest in reading after the program was implemented. Before the program, only about 49% of students had the habit of reading, while after the program was held, this figure increased to 79%. This success shows that an interactive and creative literacy environment can increase student engagement in reading and writing, as evidenced by the significant increase in the number of students who have the habit of reading by 30%. This program is expected to be a sustainable model to improve literacy in other primary schools